Ageing by feet? Regional migration, neighbourhood choice and local demographic change in German cities. Issue 6 (21st February 2018) - Neumann, Uwe
Abstract: In countries with an ageing population, regional migration affects the local consequences of demographic change. This paper investigates whether ageing implicates a more distinct residential segregation by age and results in an accelerated "ageing by feet" in urban districts not favoured by younger people. The large urban regions of North Rhine‐Westphalia in Germany serve as a case study that comprises both growing and stagnating cities. Thriving cities in the Rhineland (Bonn, Cologne and Düsseldorf) contrast with the Ruhr, where the population stagnates and ageing proceeds even more rapidly than in Germany as a whole. Intraurban variation in demographic change over the period 1998–2008 is examined using municipal statistics. The underlying segregation process is studied on the basis of a discrete choice model of neighbourhood sorting, using microdata from a representative survey carried out in the Ruhr in 2010. The analysis shows that in the course of an urban revival during the 1990s and 2000s, it was typical of individuals aged under 30 to prefer residence close to city centres. However, in the Ruhr, young adults were not underrepresented in households moving to ageing neighbourhoods that are located within a certain distance to centres either. It appears, therefore, that regional ageing will not necessarily lead to a self‐reinforcing agglomeration of young adults in the most popular central city quarters. Given a continued desire for urban centrality, however, it will become difficult for households with children to find suitable and affordable accommodation in the more central parts of large cities.